2017
DOI: 10.1007/s00468-016-1518-y
|View full text |Cite
|
Sign up to set email alerts
|

Ectomycorrhizal fungal communities of silver-fir seedlings regenerating in fir stands and larch forecrops

Abstract: the F stands was significantly higher (46) than that in the L forecrops (25), and 34% of taxa were common to both stands. The dominant ECM species in F were unidentified fungus 1, Piloderma sp., Tylospora asterophora and Russula integra. Fir seedlings regenerating in L forecrops formed ectomycorrhizas mostly with unidentified fungus 1, Tomentella sublilacina, Tylospora sp., Hydnotrya bailii and T. asterophora. Based on ANOSIM analysis, ECM communities have shown significant differences between study sites. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…Russula was also found to be a keystone taxa in the HKF network. Russula was found to be one of the most essential and abundant ECM fungi having a symbiotic relationship with diverse higher plants in the mountain rain forest, which conforms to the ndings of previous studies [22][23][24][25]. These keystone taxa in HKF play essential roles in the fungal communities of the soil environment.…”
Section: Discussionsupporting
confidence: 87%
“…Russula was also found to be a keystone taxa in the HKF network. Russula was found to be one of the most essential and abundant ECM fungi having a symbiotic relationship with diverse higher plants in the mountain rain forest, which conforms to the ndings of previous studies [22][23][24][25]. These keystone taxa in HKF play essential roles in the fungal communities of the soil environment.…”
Section: Discussionsupporting
confidence: 87%
“…( Rudawska et al, 2016 ). Besides the already listed genera, members of the genera Clavulina , Elaphomyces , Amanita , Boletus , Sebacina and Tylospora were already found to be associated and typical in silver fir stands ( Comandini et al, 1998 ; Wazny, 2014 ; Rudawska et al, 2016 ; Arguelles-Moyao et al, 2017 ; Ważny and Kowalski, 2017 ). Yet their exact role in framing the plant partner phenology remains unexplored.…”
Section: Discussionmentioning
confidence: 98%
“…The shift in EcM community associated with growth stages for South American Nothofagaceae forests has not yet been elucidated, nor the effects of site conditions or anthropogenic impacts. It has been reported that seedlings could present a reduced diversity of EcM communities compared to mature stands (Ważny and Kowalski, 2017), that some EcM species can be present at any stage of ecosystem development (Matsuda and Hijii, 2004;Twieg et al, 2007), while others has high association with seedling stages (Cline et al, 2005;Ważny and Kowalski, 2017). All these considerations should be taken in account to select candidate species for inoculation programs.…”
Section: Forestrymentioning
confidence: 99%